Rimegepant: first novel oral calcitonin gene-related peptide inhibitor for migraine - Ramasubbu, Saravana Kumar; Dakshinamurthy, Senkadhirdasan; Palepu, Sarika; Bandyopadhyay, Arkapal; Rajendran, Sathish Kumar (International Journal of Basic & Clinical Pharmacology, 2020)
Migraine is a neurological condition characterized by intense, debilitating headaches. Symptoms may include nausea, vomiting, numbness or tingling, sensitivity to light and sound. There are multitude of drugs available to treat migraine like triptans, non-steroidal anti-inflammatory drugs, ergots and opioids. But these drugs are associated with adverse effects especially triptans causing cardiovascular effects limiting its use. During last decade, calcitonin gene-related peptide (CGRP) has emerged as a possible mechanism for management of migraine. CGRP has been shown to release during episode of migraine attack and it may play a causative role in induction of migraine. Rimegepant is a novel CGRP antagonist has been approved by FDA for treatment of acute migraine. Rimegepant is a first oral CGRP antagonist compared to other gepants. The oral bioavailability of Rimegepant is 64% and high fat meal can decrease the Cmax, Tmax and area under the curve. This drug is mainly metabolized by CYP3A4 and to lesser extent by CYP2C9. Most common adverse reactions associated with this drug were nausea and urinary tract infection. Clinical trials for Rimegepant have been positive, and results suggest that the drug may be a new safe and effective option for treatment of acute migraine.